Efektivitas Pemanfaatan Komputer pada Kantor Pengadilan Tata Usaha Negara Makassar - Agiskawati, Andi; Jamaluddin, Jamaluddin; Nasrullah, Muh.; Salam, Rudi (Jurnal Office, 2018)
This study aims to determine the Effectiveness of Computer Use at the Makassar State Administrative Court. This research is quantitative descriptive. The population of this study was 54 people from the Makassar State Administrative Court. Data collection techniques using observation, questionnaire, interview and documentation techniques. Data analysis techniques used are percentage analysis in the frequency table. The results showed that the Effectiveness of Computer Use in the Makassar State Administrative Court was in the Effective category, in terms of indicator 1) The success of the program with a percentage of 87.38% was in the effective category, 2) The success of the target with a percentage of 87.04% was in the category effective, 3) Satisfaction with the program with a percentage of 85.88% in the effective category, 4) The level of input and output with a percentage of 89.81 is in the effective category, and 5) Achievement of the overall goal with a percentage of 86.92% is in the effective category.Â